The biomedical engineer’s pledge: overview and context - Antoni Ivorra; Txetxu Ausín; Laura Becerra-Fajardo; Antonio J. del Ama; Jesús Minguillón; Aracelys García-Moreno; Jordi Aguiló; Filipe Oliveira Barroso; Bart Bijnens; Oscar Camara; Sara Capdevila; Roger Castellanos Fernandez; et al. (Medical & Biological Engineering & Computing, 2026)
Although biomedical engineering (BME) is a profession with ethical responsibilities comparable to those in medicine, it has, until now, lacked a counterpart to the Hippocratic Oath. While professional societies have established codes of ethics for biomedical engineers, these documents lack the symbolic and ceremonial significance of an oath or pledge. By contrast, the recitation of the Hippocratic Oath, or its modern version, the “Physician’s Pledge,” serves as a powerful rite of passage for medical students, fostering a strong sense of ethical duty at the start of their professional journey. However, the content of the Hippocratic Oath includes elements specific to clinical practice and is not directly applicable to biomedical engineering. To fill this gap, we have created a “Biomedical Engineer’s Pledge,” comprising a preamble, ten promises, and a concluding statement, to inspire ethical awareness and establish a meaningful graduation tradition. Graphical abstract

Corrigendum to ‘A horizon scan exercise for aquatic invasive alien species in Iberian inland waters’ Sci. Total Environ.869 (2023) 161798 - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

A horizon scan exercise for aquatic invasive alien species in Iberian inland waters - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

The targeted therapy revolution in neuroendocrine tumors: in search of biomarkers for patient selection and response evaluation - Sara De Dosso; Enrique Grande; Jorge Barriuso; Daniel Castellano; Josep Tabernero; Jaume Capdevila (Cancer and Metastasis Reviews, 2013)